Alys Yn y Canol - Curtin, Judi,Huws, Eleri (Gwasg Carreg Gwalch, 2018)
Megan can't wait to go to the Summer Camp with Alys, her best friend. But when Alys meets a new friend at the camp, Megan feels left out. Eleri Huws's Welsh adaptation of Alice in the Middle by Judi Curtin.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books